Effects of Induced Emotional Changes on Bicep Brachii Muscle Activity - Sangwon Yang; Yumi Shin; Sujin Kim (Physical Therapy Korea, 2021)
Background: Studies suggest that induced emotional changes can affect the sensory-motor system involved in the practice of muscle activity and movement in physical aspects. Previous studies have shown focused on effects just feedback on muscle activity associated with emotions but rarely have focused induced emotional change on gross motor function such as muscle activity. Objects: The purpose of this study was to compare biceps activity and emotion that before and after viewing a video was induced positive or negative emotion. Methods: The study enrolled 34 healthy male and female who scored at normal points on the Center for Epidermiological Studies-Depression Scale. The study measured over two weeks, showing subjects pleasant and sad videos one by one in a week. We performed to measure the biceps brachii activity which is maximal voluntary isometric contraction (MVIC) and the visual analog mood scale (VAMS) scores before and after one week. The significance level was set to α = 0.05. Results: There was no significant difference in muscle activity of the biceps brachii before and after each video was viewed (p > 0.05). However, the visual analogue mood scale showed an increase in VAMS after viewing each video (p < 0.05). Conclusion: We figured out induced emotional changes are cause actual emotional changes but there are no differences in muscle activity. In this research, watching the video with a short time looks like insufficient to change muscle activity. Nevertheless, there might be different when we check various muscles with sufficient time for viewing the video. Further study is needed to measure a variety of muscles with more time for viewing the video.